Ethical considerations around volunteer payments in a malaria human infection study in Kenya: an embedded empirical ethics study - Chi, PC; Owino, EA; Jao, I; Bejon, P; Kapulu, M; Marsh, V; Kamuya, D (BioMed Central, 2022)
Human Infection Studies (HIS) have emerged as an important research approach with the potential to fast track the global development of vaccines and treatments for infectious diseases, including in low resource settings. Given the high level of burdens involved in many HIS, particularly prolonged residency and biological sampling requirements, it can be challenging to identify levels of study payments that provide adequate compensation but avoid 'undue' levels of inducement to participate. Through this embedded ethics study, involving 97 healthy volunteers and other research stakeholders in a malaria HIS programme in Kenya, and using in-depth interviews, focus group discussions and observations during and after a malaria HIS, we give a grounded account of ethical issues emerging in relation to study payments in this setting. While careful community, national, international scientific and ethics review processes meant that risks of serious harm were highly unlikely, the levels of motivation to join HIS seen could raise concerns about study payments being too high. Particular value was placed on the reliability, rather than level, of study payment in this setting, where subsistence livelihoods are common. Study volunteers were generally clear about the study aims at the point of recruitment, and this knowledge was retained over a year later, although most reported experiencing more burdens than anticipated at enrolment. Strict study screening procedures, regular clinical and laboratory monitoring of volunteers, with prompt treatment with antimalarial at predetermined endpoints suggested that the risks of serious harm were highly unlikely. Ethical concerns emerged in relation to volunteers' attempts to conceal symptoms, hoping to prolong residency periods and increase study payments; and volunteers making decisions that compromised important family relationships and personal values. Our findings support an interpretation that, although study volunteers were keen to join the study to access cash payments, they also paid attention to other features of the study and the general clinical research landscape, including levels of risk associated with study participation. Overall, our analysis shows that the ethical concerns emerging from the study payments can be addressed through practical measures, hinged on reducing burdens and strengthening communication, raising important issues for research policy and planning.